Formation of Sino-Arabic Calligraphy Along the Silk Route: An Interdisciplinary Study - Zekrgoo, Amir H. (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Formation of Sino-Arabic Calligraphy Along the Silk Route: An Interdisciplinary Study